Pain in systemic sclerosis - S. Stisi; P. Sarzi-Puttini; M. Benucci; G. Biasi; S. Bellissimo; R. Talotta; F. Atzeni (PAGEPress Publications, 2014)
Chronic pain is a healthcare problem that significantly affects the mental health, and the professional and private life of patients. It can complicate many disorders and represents a common symptom of rheumatologic diseases, but the data on its prevalence is still limited. Pain is a ubiquitous problem in systemic sclerosis (SSc). SSc-related pain has been studied on the basis of biomedical models and is considered a symptom caused by the disease activity or previous tissue damage. Effective pain management is a primary goal of the treatment strategy, although this symptom in SSc has not yet been investigated in detail. However, these patients do not all respond adequately to pharmacological pain therapies, therefore in these cases a multimodal approach needs to be adopted.